2010
DOI: 10.1016/j.cytogfr.2010.06.002
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB inducing kinase: A key regulator in the immune system and in cancer

Abstract: NF-κB inducing kinase (NIK) is a kinase that activates the canonical and non-canonical NF-κB pathways to control transcriptional expression of certain proteins such as cytokines, chemokines and NF-κB signaling molecules. Many advances have been made in understanding the molecular mechanisms by which the stability of NIK is regulated to affect downstream signaling. Genetic mouse models suggest that NIK has an essential role in regulation of the immune system as well as in the bone microenvironment. Increasing e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
112
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(114 citation statements)
references
References 120 publications
(302 reference statements)
2
112
0
Order By: Relevance
“…Interestingly, ligand-dependent or -independent LT␤R internalization might be linked to cancer progression. Indeed, we showed that dynamin-dependent internalization of LT␤R is required for NIK stabilization, and exacerbated accumulation of NIK has been reported in hematopoietic as well as nonhematopoietic cancer cells (50). For instance, liver-specific LT␣/LT␤ expression leads to hepatitis-induced hepatocellular carcinoma development and this phenotype can be reversed when mice are treated with Fc-LT␤R recombinant decoy receptors (18).…”
Section: Discussionmentioning
confidence: 77%
“…Interestingly, ligand-dependent or -independent LT␤R internalization might be linked to cancer progression. Indeed, we showed that dynamin-dependent internalization of LT␤R is required for NIK stabilization, and exacerbated accumulation of NIK has been reported in hematopoietic as well as nonhematopoietic cancer cells (50). For instance, liver-specific LT␣/LT␤ expression leads to hepatitis-induced hepatocellular carcinoma development and this phenotype can be reversed when mice are treated with Fc-LT␤R recombinant decoy receptors (18).…”
Section: Discussionmentioning
confidence: 77%
“…In some cases, genetic alterations such as gene amplifications, translocations, or mutations in NIK, or alterations in genes regulating the stability of NIK protein, are described, emphasizing the role of NIK in tumorigenesis (14,19,34). From previous reports, the role of NIK in the alternative NF-kB pathway is clear, but the involvement of NIK in the regulation of the classical pathway seems to be signal and cell type dependent (13,35). For example, in melanoma and pancreatic cancer, NIK only affects the alternative pathway (22,36), whereas NIK regulates both pathways in DLBCL and multiple myeloma (14,16).…”
Section: Discussionmentioning
confidence: 99%
“…In melanoma, constitutive activation of NF-κB is responsible for CXCL1 production [20,21] and in acute myelogenous leukemia high levels of the transcription factor MEF2C induce over-expression of CCL2, CCL3 and CCL4 [22]. CXCR4 and CCR5 can also be transactivated by the Insulin-like Growth Factor-1 or via its receptor [23,24].…”
Section: Chemokines As Targets Of Genetic Lesions Causing Cancermentioning
confidence: 99%